Genetic diversity of garut mutant (Maranta arundinacea L.) (M3) with random amplified polymorphic DNA (RAPD) analysis - Paradisa, Yashanti Berlinda; Deswina, Puspita; Priadi, Dodi; Anggraheni, Yuliana Galih Dyan; Nurbaeti, Santi; Chaidir, Liberty; Wicaksana, Noladhi (Penerbit Universiti Kebangsaan Malaysia, 2025)
Arrowroot is a type of tuber that is rich in carbohydrates. This plant can grow well in various parts of Indonesia. However, arrowroot has a low level of genetic diversity, making it difficult to obtain superior varieties with high productivity. Mutation treatment with gamma-ray radiation is expected to increase the diversity of arrowroot to produce superior-quality plants. This study aimed to determine the genetic diversity of arrowroot mutants resulting from the 4th generation of gamma-ray radiation (M3). The research analysed molecular markers using Random Amplified Polymorphic DNA (RAPD). A total of 30 samples of arrowroot M3 DNA were amplified using 11 selected primers. The results of the analysis show that there are six specific primers selected from the selection, which have the potential to produce high polymorphism bands that can be used for diversity analysis. The similarity index of arrowroot mutant is 0.69 to 0.99, which means that it still has a high similarity between arrowroot mutant. Based on genetic similarity of 84%, mutant arrowroot (M3) can be divided into 7 clusters.